ANALISIS PENGEMBANGAN BISNIS DENGAN MENGGUNAKAN BMC (BUSINESS MODEL CANVAS) - Elka Pratama, Adam; Yuana, Pusvita (Jurnal Kewirausahaan dan Inovasi, 2022)
The research entitled "Analysis of Business Development Using the BMC (Business Model Canvas) Method for Anugerah Jaya Photo Copy Business" aims to formulate a new business model and also carry out business development on Anugerah Jaya Photo Copy. The method used in conducting this research is a qualitative method, while the data collection for processing carried out in this research is by means of interviews, questionnaires, and observations. Business development aims to find out what a company needs to increase the existing revenue in a company. The existence of a new business model formulation technique using the BMC (Business Model Canvas) method aims to map out what a company will need to develop its business. The formulation of the new business model in Anugerah Jaya Photocopy is useful for developing businesses that have been running so far. With the formulation of the new business model, Anugerah Jaya Photo Copy can see what will be needed to develop the business.